2020
DOI: 10.3390/cancers12020386
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Comprehensive Clinical Stratification Model to Refine Prognosis of Glioblastoma Patients Undergoing Surgical Resection

Abstract: Despite recent discoveries in genetics and molecular fields, glioblastoma (GBM) prognosis still remains unfavorable with less than 10% of patients alive 5 years after diagnosis. Numerous studies have focused on the research of biological biomarkers to stratify GBM patients. We addressed this issue in our study by using clinical/molecular and image data, which is generally available to Neurosurgical Departments in order to create a prognostic score that can be useful to stratify GBM patients undergoing surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 57 publications
(95 reference statements)
1
20
1
Order By: Relevance
“…For this reason, it is incredibly important to achieve the most extensive resection feasible. It has been repeatedly demonstrated that the extent of resection (EOR) is directly related to the outcome of treatment of patients with gliomas and is an important predictive factor [ 33 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. For glioblastoma, Stummer et al showed the effect of EOR on 6 months of PFS (progression-free survival) in the range of 21.1 to 41% [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is incredibly important to achieve the most extensive resection feasible. It has been repeatedly demonstrated that the extent of resection (EOR) is directly related to the outcome of treatment of patients with gliomas and is an important predictive factor [ 33 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. For glioblastoma, Stummer et al showed the effect of EOR on 6 months of PFS (progression-free survival) in the range of 21.1 to 41% [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methods of this study were based on a previous study in which a scoring system for patients of all ages with GBM was elaborated. 21…”
Section: Methodsmentioning
confidence: 99%
“…To determine subgroup patients with different clinical prognoses, we used the decision tree model with the classification and regression tree (CART) method. 21,26 This method is a machine learning model composed of hierarchical decision rules involving optimal cutoff values that recursively split independent factors into different groups. The groups of individuals are called nodes and form a branch node tree.…”
Section: Classification and Regression Tree Methodsmentioning
confidence: 99%
See 2 more Smart Citations